Penggunaan Metode Number Head Together (NHT) dalam meningkatkan Prestasi Belajar Matematika Materi Pengukuran Siswa Kelas III di SD Swasta Pekalongan - Aqida, Debbi Silvia (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This article intends to show the effectiveness of the use of the NHT method on mathematics achievement in measuring material. The problem in this research is that the mathematics learning achievement of third grade students at Pekalongan Private Elementary School is still low, especially in measurement material, indicated by the average score of mathematics learning achievement of 71.38 (with KKM 75). The purpose of this study was to improve the mathematics learning achievement of class III students of Pekalongan Private Elementary Schools using the Numbered Head Together (NHT) learning method. Through the NHT (Numbered Head Together) learning method, assignments are given to all students where students have been given different numbers in their groups but each group uses the same numbering. Calling student numbers randomly to report the results of group discussions encourages each student individually to take responsibility for their learning outcomes. This research is a class action research using a qualitative descriptive research method, with the type of field research. Data collection techniques using interviews, observation, and documentation. Data analysis techniques using Miles and Huberman. As a result, of the 12 students before receiving learning with the NHT (Numbered Head Together) method, it can be seen from the three indicators of achievement in learning mathematics (cognitive, affective, psychomotor) that did not show well. After students receive learning with the NHT (Numbered Head Together) method, three indicators (cognitive, affective, psychomotor) show an increase as evidenced by the achievement in learning mathematics, the better the measurement material.